2020
DOI: 10.1002/jbmr.4102
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Metabolite Network Linked to Inhibited Bioenergetics in Association With Spaceflight-Induced Loss of Male Mouse Quadriceps Muscle

Abstract: Prolonged residence of mice in spaceflight is a scientifically robust and ethically ratified model of muscle atrophy caused by continued unloading. Under the Rodent Research Program of the National Aeronautics and Space Administration (NASA), we assayed the large-scale mRNA and metabolomic perturbations in the quadriceps of C57BL/6j male mice that lived in spaceflight (FLT) or on the ground (control or CTR) for approximately 4 weeks. The wet weights of the quadriceps were significantly reduced in FLT mice. Nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
6
18
0
Order By: Relevance
“…Therefore, it is unlikely that the transcriptome alterations we characterized are simply a product of the age of the mice employed. In fact, investigations of microgravity-induced differential gene expression in younger mice (Gambara et al, 2017;Chakraborty et al, 2020) showed downregulation of metabolic and mitochondrial pathways similar to what we identified in our older mice. Therefore, while AS has not been adequately investigated in the context of spaceflight, it can be speculated that extensive microgravity-induced AS would be identified regardless of age.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Therefore, it is unlikely that the transcriptome alterations we characterized are simply a product of the age of the mice employed. In fact, investigations of microgravity-induced differential gene expression in younger mice (Gambara et al, 2017;Chakraborty et al, 2020) showed downregulation of metabolic and mitochondrial pathways similar to what we identified in our older mice. Therefore, while AS has not been adequately investigated in the context of spaceflight, it can be speculated that extensive microgravity-induced AS would be identified regardless of age.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the presence of a microgravity-induced slow-to-fast fiber transition suggests that, despite the opposing force of aging on fiber type composition, the slow-to-fast fiber plasticity of skeletal muscle fibers is maintained even at an increased age. In contrast to fiber transitions, aging mirrors the effect of microgravity on muscle atrophy (Ohlendiek, 2011); it is possible that the advanced age of our mice compared to early age mice in other studies (Harrison et al, 2003;Gambara et al, 2017;Camerino et al, 2013;Chakraborty et al, 2020) amplified the microgravity-induced atrophy that was observed here. Most important to our work, however, is the relationship between modes of transcriptomic regulation and age.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…66 Our findings support emerging spaceflight evidence that altered bioenergetic forms a universal cellular response to microgravity. 67 To further identify novel mechanosensitive gene(s), we compared gene datasets available in the NASA GeneLab database. We identified two upregulated genes and eight downregulated genes in-flight vs ground (Table 1).…”
Section: Discussionmentioning
confidence: 99%